"You produce while I clean up", a strategy revealed by exoproteomics during Synechococcus–Roseobacter interactions. Issue 20 (21st April 2015) - Christie‐Oleza, Joseph A.; Scanlan, David J.; Armengaud, Jean; Jagtap, Pratik; Griffin, Tim; Armengaud, Jean
<x xml:space="preserve">Abstract</x> Most of the energy that is introduced into the oceans by photosynthetic primary producers is in the form of organic matter that then sustains the rest of the food web, from micro to macro‐organisms. However, it is the interactions between phototrophs and heterotrophs that are vital to maintaining the nutrient balance of marine microbiomes that ultimately feed these higher trophic levels. The primary produced organic matter is mostly remineralized by heterotrophic microorganisms but, because most of the oceanic dissolved organic matter is in the form of biopolymers, and microbial membrane transport systems operate with molecules <0.6 kDa, it must be hydrolyzed outside the cell before a microorganism can acquire it. As a simili of the marine microbiome, we analyzed, using state‐of‐the‐art proteomics, the exoproteomes obtained from synthetic communities combining specific Roseobacter (Ruegeria pomeroyi DSS‐3, Roseobacter denitrificans OCh114, and Dinoroseobacter shibae DFL‐12) and Synechococcus strains (WH7803 and WH8102). This approach identified the repertoire of hydrolytic enzymes secreted by Roseobacter, opening up the black box of heterotrophic transformation/remineralization of biopolymers generated by marine phytoplankton. As well as highlighting interesting exoenzymes this strategy also allowed us to infer clues on the molecular basis of niche partitioning.